2020
DOI: 10.4103/jips.jips_282_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between maximum occlusal force and median mandibular flexure in adults: A clinical trial study

Abstract: Aim: The narrowing of the mandible during opening and protrusion movements is defined as median mandibular flexure (MMF). MMF is caused by the attachment of mandibular muscles; therefore, it can be assumed that a greater amount of maximum occlusal force (MOF) may cause more flexion and could affect the survival of dental and implant restorations. The purpose of this study was to evaluate any relationship between MOF and MMF in a sample of adults. Settings and Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(17 reference statements)
0
4
1
Order By: Relevance
“…In addition, the deviation values in the anterior measuring reference aid (canines) were less than those recorded in the posterior reference aids (molars). The results of this study showed no statistical difference in mandibular deviations between males and females, despite those other reports indicating more flexure in females [ 28 30 ].…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, the deviation values in the anterior measuring reference aid (canines) were less than those recorded in the posterior reference aids (molars). The results of this study showed no statistical difference in mandibular deviations between males and females, despite those other reports indicating more flexure in females [ 28 30 ].…”
Section: Discussioncontrasting
confidence: 96%
“…However, no age difference was identified in the MMF evaluation between the two groups in the research by Gülsoy et al, where the average age of the edentulous individuals was 63 years and that of the dentate participants was 29 years ( p > 0.05) [ 75 ]. Even though the age–mandibular flexion correlation has not been proven in numerous articles with statistically significant results, the studies showing its interdependence can be explained by the connection between age-related consequences (lower bone density and smaller symphysis structure) and mandibular deformation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic models made from imprints obtained at various phases of the mandibular opening were frequently used to make in vivo extra-oral measurements, as were photos that monitored the movement of the mandibles [ 10 , 15 , 30 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the positive correlation between masticatory muscle strength and occlusal force ( van der Bilt et al, 2006 ; Ebadian et al, 2020 ) evaluated the relationship between mandibular occlusal force (MOF) and MMF in a cohort of adult participants, revealing that MOF and MMF are critical and effective factors in the success of prosthetic restorations. Nonetheless, ( Canabarro Sde and Shinkai, 2006 ), employed a distinct methodology in their study, which collected bilateral MOF measurements using transarch force transducers positioned in the first molar region.…”
Section: Mmfmentioning
confidence: 99%